151k views
3 votes
3. Which of the equations below is not equivalent to -3 + 2y = * = 6?

User JosieP
by
4.7k points

1 Answer

2 votes

The equation is given as ;

-3+2y - 1/3 x =6

collect like terms as;

2y = 1/3 x + 6 +3

2y = 1/3 x + 9 ----divide each term by 2

y= 1/6 x + 9/2 -----the equation in slope -intercept form

Here you have a slope , m, of 1/6 and y-intercept of 9/2

From the equations given in the answer choices, you can check one by one as;

In A.

-x+6y=27

6y = x+ 27

y=1/6 x + 27/6

y= 1/6 x + 9/2 ------Answer option A is equivalent to our equation so this is not the correct answer.

In B.

6y=27 + x

y=1/6 x + 27/6

y= 1/6 x + 9/2 -------Answer option B is equivalent to our equation so this is not the correct answer.

In C.

2y - x =27

2y = x + 27

y= 1/2 x + 27/2 -------Answer option C is not equivalent to our equation so this is the correct answer

Answer : C : 2y-x=27

User Tgrez
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.